Cellular therapies based on stem cells and their insulin‐producing surrogates: a 2015 reality check. Issue 3 (5th February 2015) - Giannoukakis, Nick; Trucco, Massimo
<x xml:space="preserve">Abstract</x> Stem cell technology has recently gained a substantial amount of interest as one method to create a potentially limitless supply of transplantable insulin‐producing cells to treat, and possibly cure diabetes mellitus. In this review, we summarize the state‐of‐the art of stem cell technology and list the potential sources of stem cells that have been shown to be useful as insulin‐expressing surrogates. We also discuss the milestones that have been reached and those that remain to be addressed to generate bona fide beta cell‐similar, insulin‐producing surrogates. The caveats, limitations, and realistic expectations are also considered for current and future technology. In spite of the tremendous technical advances realized in the past decade, especially in the field of reprogramming adult somatic cells to become stem cells, the state‐of‐the art still relies on lengthy and cumbersome in vitro culture methods that yield cell populations that are not particularly glucose‐responsive when transplanted into diabetic hosts. Despite the current impediments toward clinical translation, including the potential for immune rejection, the availability of technology to generate patient‐specific reprogrammable stem cells has, and will be critical for, important insights into the genetics, epigenetics, biology, and physiology of insulin‐producing cells in normal and pathologic states. This knowledge could accelerate the time to reach the desired breakthrough for safe and efficacious beta cell surrogates.